Determinants of Length of Stay Among Neonates Admitted to the Neonate Unit, Wajir County Referral Hospital, Kenya - Sheikh, Daud Abdi (Amref International University, 2024)
Background: Prolonged hospital length of stay for neonates is a concern in public health as it exposes them to infection and increases healthcare costs. This contributes to mortality. Objective: To establish the determinants of length of stay among neonates admitted at the neonate unit at Wajir County Referral Hospital, Kenya. Methodology: A cross-sectional research design was used, and 138 mothers with admitted infants were interviewed. Data was collected using a structured questionnaire and analyzed using SPSS version 26.0. Descriptive and inferential analyses were applied to determine the determinants of length of stay for neonates. Results: Age of the mother (𝒳2 = 10.213; p-value=.001) and occupation (𝒳2 = 𝑑𝑓=1 𝑑𝑓=1 4.408 ; p-value=.036) were the socio-demographic characteristics that yielded an association that was statistically significant with duration of stay in the neonate unit. Distance to hospital from home (𝒳2 𝑑𝑓=4 = 46.499; p-value < .0001), quality of service ( 𝒳2 = 52.951 ; p-value < .0001) and staff attitude ( 𝒳2 = 28.934 ; p-value < 𝑑𝑓=2 𝑑𝑓=2 .0001) were the institutional determinants whose effect was statistically significant on neonates’ length of stay in Wajir County Referral Hospital’s New-born Unit. Parity (𝒳2 = 11.920; p-value = .003), pregnancy interval (𝒳2 = 11.333; p-value=.003), 𝑑𝑓=2 𝑑𝑓=2 comorbidity conditions ( 𝒳2 𝑑𝑓=1 = 15.613 ; p-value < .0001), number of ANC visits (𝒳2 = 29.447; p-value < .0001) and mode of delivery (𝒳2 = 4.642; p-value = 𝑑𝑓=1 𝑑𝑓=1 .031) were the maternal determinants that had a significant association with LOS for neonates. Complications during pregnancy ( 𝒳2 = 29.311 p-value < .0001), 𝑑𝑓=1 complications during delivery (𝒳2 𝑑𝑓=1 = 23.024; p-value < .0001), complications after delivery (𝒳2 = 5.187; p-value = .023), weight at birth (𝒳2 = 92.301; p-value < 𝑑𝑓=1 𝑑𝑓=1 .0001), and child born with complications (𝒳2 𝑑𝑓=1 = 34.043; p-value < .0001) were the neonates’ risk factors that had a statistically significant association with LOS for neonates. Conclusions: The study concludes that select socio-economic factors are associated significantly with neonatal length of stay, suggesting a similarity in backgrounds among admitted neonates. Institutional factors like proximity to healthcare facilities, service quality, and staff attitude had a significant association with neonates’ length of stay. Maternal risk factors such as parity, pregnancy interval, comorbidity conditions, antenatal care visits, and delivery mode were associated significantly with neonates’ length of stay. Neonates’ risk factors, such as complications during pregnancy and delivery and after delivery, birth weight, and child born with complications, have a significant effect on neonates’ length of stay. Recommendations: The study recommends adopting measures to ensure equitable access to healthcare in marginalized communities in Wajir County. Continuous training for healthcare workers on patient complaint management and prioritizing ambulance availability are advised to improve service quality and reduce poor outcomes, especially in emergencies, positively impacting LOS. Furthermore, the study recommends optimizing hospital resources and infrastructure to ensure timely and efficient delivery of neonatal care services.
A Research Thesis Submitted in Partial Fulfilment for the Degree of Masters in Public Health (Applied Epidemiology), Department of Community Health, School of Public Health, Amref International University
Keywords: Neonate